Revealing species identity of edible razor clam Cultellus sp. (Bivalvia: Pharidae) from Madura Island, Indonesia - RENI AMBARWATI; DWI ANGGOROWATI RAHAYU (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ambarwati R, Rahayu DA. 2024. Revealing species identity of edible razor clam Cultellus sp. (Bivalvia: Pharidae) from Madura Island, Indonesia. Biodiversitas 25: 1505-1513. Razor clams have an essential role as commercial commodities. One of the poorly-known edible razor clams from Madura, Indonesia, has not been identified as the species. This research aimed to identify the edible razor clam (Bivalvia: Pharidae) species from Madura Island, Indonesia. The samples of razor clams (Cultellus sp.) were collected from Bangkalan, Madura Island, Indonesia. Identification was conducted based on morphological and molecular characterization. The foot tissues of three individuals were processed for DNA isolation, electrophoresis, amplification, and sequencing to obtain the sequences of COI gene. The morphological characters of razor clam shells were analyzed descriptively and quantitatively. Data were collected from the COI gene sequences of razor clam Cultellus sp. and descriptively analyzed using bioinformatics software. The morphological identification revealed razor clams (Cultellus sp) from Bangkalan, Madura, Indonesia, Cultellus subellipticus. The nucleotide base composition sequences of C. subellipticus A, B & C consisted of Thiamine (T), Cytosine (C), Adenine (A), and Guanine (G) with a mean of 18.25, 12.92, 23.42, and 46.39%. Maximum Likelihood (ML) and Minimum Evolution (ME) phylogenetic analysis was also conducted using the Kimura 2 Parameter model to establish one major clade on C. subellipticus from the gene bank and a different group with Cultellus attenuatus and one out-group significantly different from the Ensis macha. This finding was strengthened by molecular identification results, which indicated the similarity with C. subellipticus from GenBank, with very high BOLD System data between 98.10-98.86%.